The migration policy of Armenia - Gomólka, Krystyna (Przegląd Politologiczny, 2018)
The aim of this study is to describe the legal bases of the migration policy of Armenia and its practical implementation in 1995–2013. The author examined the international and national documents that provide the legal bases of Armenia’s migration policy, as well as the balance between departures and arrivals in the period 1995–2013, Armenian citizens’ reasons for emigrating and the occupations of emigrants. The study was based on the following research methods: content, system and quantitative analysis. The results of the analyses performed indicate that the objectives of Armenia’s migration policy were not completely fulfilled. Between 1995 and 2013, the number of emigrants declined, but Armenia’s overall migration balance was negative. The majority of those leaving the country went to Russia, followed by the other states of the CIS.